Aerodynamic interferance effects of two interfering buildings on the characteristics of wind force on a tall building - Kittikarn Maneekad; Pennung Warnitchai; Punchet Thammarak; Thanakorn Pheeraphan; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
The aerodynamic interference effect of the two interfering buildings was investigated by the experiment in wind tunnel. The building models were tested in the boundary layer of sub-urban condition. The dimensions of both principle and interfering buildings model were based on the recommendation of the Commonwealth Advisory Aeronautical Research Council (CAARC). The isolated building was measured the responses by using the high-frequency force balance (HFFB) technique for checking the results of HFPI technique. The side-by-side arrangement of the two upstream interfering buildings will be placed in the different grid locations around the principle building. There are six cases of the upstream interfering building arrangement. The spacing between the buildings (both interfering buildings and principle building) will be varied on the grid location. Wake boundary of the two upstream buildings was investigated by using hot-wire anemometer to measure the fluctuating wind velocity which was employed to calculate the turbulence intensity, Iu, of the wake of each case. The across-wind, along-wind and torsional response of the principle building were measured by using the high-frequency pressure integration (HFPI) technique in a boundary layer inside the wind tunnel and the pressure taps were installed to determine the variable pressure on the principle building. The interference effect was expressed in terms of interference factor. The response of building was separated into 3 components. The interference factor of mean, background and resonant responses will be plotted in the separated contour maps. The obtained interference factor contour show the downstream critical areas of the two interfering where the total response can be significantly amplified (greater than 20% of isolated case). The increase of response mainly depend on the increase of resonant response. Most critical area of response in along wind direction can be found at the region near edge of the wake boundary. For across wind direction, most critical areas were found at the side of the interfering building. The response in torsional direction can be observed at the region behind the interfering building.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2017
Keywords: Tall buildings -- Aerodynamics; Buildings -- Wind stresses